Security in Smart Cities: Models, Applications, and Challenges - Hassanien, Aboul Ella; Elhoseny, Mohamed; Ahmed, Syed Hassan; Singh, Amit Kumar (Lecture Notes in Intelligent Transportation and Infrastructure, 2019)
VIII, 364 p. 150 illus., 84 illus. in color.